2020
DOI: 10.1029/2020gl090856
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the Summer Monsoon in Generating Streamflow Within a Snow‐Dominated Headwater Basin of the Colorado River

Abstract:  Monsoon rains generate 10±6% of annual streamflow while late spring snowfall delivers twice as much for the same water input.  The influence of monsoon rain on streamflow is half of late spring snow due to evapotranspiration in the lower subalpine forest.  Monsoon efficiency in generating streamflow decreases in warm years with low snow accumulation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Specifically for the East River, our findings corroborate hydrologic modeling results that showed that most rain gets evapotranspired, and little rain becomes runoff to the East River (Carroll et al., 2020). Our estimate of ∼7% of total Q stemming from rain for the East River at Pumphouse is within the range of modeled estimates (∼10%, Carroll et al., 2020). Our findings support ET source water estimates from particle tracking simulations, which indicated that ET of a forested hillslope in the East River catchment was to large parts sourced by snowmelt (Maxwell et al., 2019).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically for the East River, our findings corroborate hydrologic modeling results that showed that most rain gets evapotranspired, and little rain becomes runoff to the East River (Carroll et al., 2020). Our estimate of ∼7% of total Q stemming from rain for the East River at Pumphouse is within the range of modeled estimates (∼10%, Carroll et al., 2020). Our findings support ET source water estimates from particle tracking simulations, which indicated that ET of a forested hillslope in the East River catchment was to large parts sourced by snowmelt (Maxwell et al., 2019).…”
Section: Discussionsupporting
confidence: 89%
“…That our results are at the upper limit is due to the relatively high P S / P R ratio in our high‐elevation study area compared to other regions in the western US (Li et al., 2017). Specifically for the East River, our findings corroborate hydrologic modeling results that showed that most rain gets evapotranspired, and little rain becomes runoff to the East River (Carroll et al., 2020). Our estimate of ∼7% of total Q stemming from rain for the East River at Pumphouse is within the range of modeled estimates (∼10%, Carroll et al., 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While we can only qualitatively constrain the increased use of summer rain, this result highlights how access to this additional moisture source could have acted to mitigate stress even though snowpack was still the principal water source. The importance of summer rain outside of the core monsoon zone is often overlooked because it is snowmelt that predominantly recharges the region's aquifers and drives streamflow (Carroll et al, 2020). If monsoon circulation and summer rains increase in response to warming, as has occurred during other warm periods, then the results suggest that forest ecosystems in this region could be resilient to moisture stress associated with warming.…”
Section: Discussionmentioning
confidence: 99%
“…During drought years, additional precipitation (especially monsoon) plays a vital role in restoring ET and compensating for the loss of ET during the preceding dry periods. Carroll et al (2020) found that drought conditions modify monsoon precipitation's contributions to ET and streamflow. Their study suggested that monsoon precipitation is mainly effective in moistening dry soil and sustaining ET at lower subalpine forests during dry years, while being the primary contributor to streamflow generation under normal/wet year conditions.…”
Section: Assessing Et Inter-annual Variability Through Identifying Re...mentioning
confidence: 99%